Contributions et démarche de l’ergonomie dans les processus de conception - Alain Garrigou; Jean-François Thibault; Marçal Jackson; Fausto Mascia (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article proposes an industrial ergonomic design process that links three approaches :• a top-down approach that corresponds to a classical design phase in which the ergonomist will interact with the designers, in particular upstream from the projects ;• a bottom-up approach, during which feedback will be analyzed in existing situations in order to enhance the needs analysis and produce scenarios of future activities ;• a simulation approach which, by interacting with the two approaches presented above, and due to the participation of representatives of the different users of the future equipment, will allow the operators’ future activity to be co-constructed and the designers’ proposals to be evaluated.The ergonomists’ contributions are discussed from an analysis of the projects in which the authors participated. This provides a broader view of the question of the evolution of ergonomists’ practice in the design process and identifies new challenges for ergonomics.